Genomic characterization of APEC phages and evaluation of the efficacy in reducing the loads of APEC O78 infections in chickens - Lu, Qin; Jin, Xinxin; Wang, Zui; Zhang, Rongrong; Guo, Yunqing; Hu, Qiao; Zhang, Wenting; Zhang, Tengfei; Luo, Qingping (Frontiers in Microbiology, 2026)
IntroductionThe resistance of avian pathogenic Escherichia coli (APEC) poses a serious challenge to the control of bacterial diseases in the poultry industry. Identification of useful phages as alternatives to antibiotics for APEC O78 is a priority.MethodsThe phage LQ5 was isolated from the contents of the chicken intestines. Whole-genome sequencing was performed using the Illumina NovaSeq 2500 platform, and then bioinformatics analysis was conducted on the genome. The application effect of LQ5 in the O78 infection model of chickens was systematically evaluated.ResultsThe phage LQ5 was identified as a member of Myoviridae by electron microscopy. Whole-genome sequencing showed that phage LQ5 is a double strand DNA virus with a genome of 171,908 bp containing active components, such as endolysin, holin lysis mediator. Comparison of the bacterial load of APEC in chicken liver and spleen tissue in samples treated with phage LQ5 and Amoxicillin showed that the phage LQ5 reduced the bacterial load compared with the antibiotic.DiscussionThese results have enriched the information of the phage gene bank for APEC, laying the foundation for the development of targeted phage biocontrol agents against the APEC O78 strain.